(untitled) (Research, Society and Development, 2020)
The objective of the research was to study the effect of substitution of maize for maize germ meal in laying European quail diets. 240 female quails were used in a randomized design with three treatments and eight replications, containing 10 birds per plot. The treatments consisted of a maize and soybean meal-based reference diet and two levels of substitution of maize for maize germ meal, 50 and 100%. Evaluated parameters were: number of eggs per bird housed, laying rate, feed intake, feed conversion, weight of egg, yolk, albumen and shell, and yolk pigmentation. Parameters were evaluated using analysis of variance and Tukey test, with the significance level set at 5%. In the two laying cycles studied there was a difference in the number of eggs, percentage of laying, feed conversion, weight of egg, yolk and shell and yolk pigmentation. The replacement of maize by maize germ meal in diets for laying European quail can be carried out up to 100%, producing improvement in the productive performance of the birds and in egg quality.